'No more Turkish music!' The acculturation strategies of teachers and ethnic minority students in Flemish schools. Issue 8 (20th June 2016) - Van Praag, Lore; Stevens, Peter A.J.; Van Houtte, Mieke
ABSTRACT: While considerable research has focused on the process and factors affecting acculturation, there is little research that investigates how members of minority and majority groups define acculturation in educational settings. Ethnographic research and qualitative interviews in three secondary schools in Flanders (Belgium) show that teachers and ethnic minority students have different ideas and expectancies regarding the concept 'integration', which appears to affect student–teacher relationship. Berry et al.'s [1989. "Acculturation Attitudes in Plural Societies." Applied Psychology: An International Review 3 (2): 185-206. doi:10.1111/j.1464-0597.1989.tb01208.x .] acculturation orientations are used as a theoretical template to analyse teachers' and ethnic minority students' discourses about acculturation. Analyses reveal that students of immigrant descent perceive acculturation mainly in terms of the establishment of intergroup contact. In contrast, teachers find it harder to disconnect cultural maintenance from contact and participation. By suggesting some form of cultural adoption, teachers hope to socialise their ethnic minority students into the culture of the dominant ethnic group and prepare them for their future. These distinct interpretations of 'integration' in everyday life (which actually refers to acculturation) often leads to misunderstandings between ethnic minority students and their teachers, even to conflict, as many students feel that their cultural background is disparaged and not fully valued in school.